Accountability no contexto partidário - Gil, Juliana Braga (2016)
This present work is theoretical in nature, presented in dissertation format, divided into three chapters articulated by literature review. It has the general objective to analyze the dimensions of accountability in Brazilian party context and its possible applications against corruption as a way to complement the legislative effectiveness of party responsibility. In the representative democracy context, the dimensions of vertical, horizontal and societal accountability, along with theoretical aspects of political parties and the need for specific legislation of party control, these was the theoretical axes discussed. The main objective was divided into three specific objectives, namely: i) analyze the accountability mechanisms. ii) identify and systematize conceptual and theoretical elements of political parties. iii) analyze the Brazilian legislation in terms of party responsibility and legislative advances to control corruption. In the first chapter, from the representative democracy context, it was sought to present the accountability theory, its historical perspective, its conceptual and theoretical aspects classic and its dimensions more accepted in the literature. The second chapter it was based on the origin of political parties unfolding in the dimensions of accountability for parties. Finally, in the third chapter, the laws are approached dealing with political parties and party responsibility, with emphasis on the Electoral Code of 1965, in the Federal Constitution of 1988 and in the Organic Law of Political Parties of 1995. Concludes the chapter with the Law 12.846 of 2013 analysis, known as "Anti-Corruption Law" which deals with administrative and civil responsibility of legal entities by practice acts against Public Administration, national or foreign, unfolding in action against corruption of the Federal Public Ministry, proposed in 2015.